Stock Liquidity and Return Distribution in Emerging Market - Eka Puspita Sari (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
Purpose: This study aims to illustrate the relationship between the liquidity of a stock and the return distribution of all companies listed on the Indonesian Stock Exchange. Design/methodology/approach: The correlation between stock liquidity and return distribution, represented using skewness and kurtosis methods, was determined by the author through two-way tests using line regression (fixed cross-section regression) and machine learning (random forest regressor) for Indonesia data Stock exchange from 2014 to 2023. Findings: The results indicate a connection between stock liquidity and return distribution. When evaluating stock liquidity, the zero return days technique gives a more significant relationship, while the kurtosis of return method gives a more significant return distribution. It is impossible to determine with absolute certainty whether the correlation is positive or negative; it depends on how stock liquidity and return distribution are measured. Research limitations/implications: The correlation between stock liquidity and return distribution cannot be characterized as an absolute relationship due to the intricacy and variety of approaches used to measure it. Practical implications: The kurtosis of return has a better relationship with stock liquidity, and “zero return day” and “relative spread” are still more strongly correlated with the return distribution. Originality/value: As the first study to use machine learning and linear regression to examine the relationship between stock liquidity and return distribution, this paper expands the body of knowledge. Second, it examines which return distribution – skewness or kurtosis – has a stronger correlation with stock liquidity. Third, we examine which liquidity metrics—relative spread, Amihud liquidity, price impact ratio, and zero return days—are most related to the return distribution.